PENGARUH PEMBERIAN KOMPOS LIMBAH JAGUNG DAN PUPUK FOSFOR TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays var SaccharataSturt.) - Manotar A P Manurung; Nurbaiti Nurbaiti; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
This study aims to determine the effect of the interaction of corn waste compost and phosphorus fertilizer, corn waste compost, phosphorus fertilizer application, and get a better dose of corn waste compost and phosphorus fertilizer on the growth and production of sweet corn plants. This research was carried out experimentally in the field using a factorial randomized block design (RBD), namely corn waste compost (0, 2.5, 5, and 7.5 tons.ha-1) and phosphorus fertilizer (200, 300 and 400 kg.ha-1). The parameters observed were plant height, stem diameter, number of leaves, time appears the female flowers, age of harvest, weight per cob with cornhusk, production per ha, weight per cob without cornhusk, number of rows of seeds per cob, and number seeds per row. The data obtained were statistically analyzed by analysis of variance and continued with Duncan's New Multiple Range Test (DNMRT) at the level of 5%. The results showed that there was an interaction of corn waste compost and phosphorus fertilizer in the production parameters per ha of sweet corn plants. Corn waste compost can increase plant height, stem diameter, weight per cob with cornhusk, and production per ha. The best gave is in the treatment of 7.5 tons.ha-1. The application of phosphorus fertilizer can increase plant height, stem diameter, time appears the female flowers, age of harvest, weight per cob with cornhusk, and production per ha. The best gave is in the treatment of 400 kg.ha-1. The application of 7.5 tons.ha-1 corn waste compost with 400 kg.ha-1 phosphorus fertilizer showed better results in almost all parameters, except for the number of leaves,number of rows of seeds per cob, and number seeds per row. Keywords: sweet corn, corn waste compost and phosphorus fertilizer